Morphometric Study of the Valves of Heart, A Cadaveric, Comparative Study in Karachi (Medical Forum Monthly, 2024)
Objective: Analyze cadaveric based data of valves of heart and compare data between male and females of KarachiStudy Design: Descriptive / cross sectional studyPlace and Duration of Study: This study was conducted at the Department of Anatomy, Dow Medical College, DUHS, Karachi from 2008 to 2012Materials and Methods: The hearts of one hundred cadavers (both male and female) were obtained from the morgue of Civil Hospital and other morgues of the Karachi. The hearts were removed in the usual necropsy procedure. Male and female cadaveric hearts were divided into six groups which were constituted ranging in age from 20 to 79 years i.e. Group A: 20-29, Group B: 30-39, Group C: 40-49, Group D: 50-59, Group E: 60-69 and Group F: 70-79. Young and otherwise healthy individuals (died due to road traffic accident, Gunshot injury, Suicide or Homicide) were included in the study. The cadaver whose cause of death was known to be cardiac was not included in the studyResults: The mean circumference of tricuspid valve showed a significant p-value (P- < 0.05) except age Group F. Mean circumference of mitral valve showed a significant p-value (P- < 0.05) in all groups. Mean circumference of pulmonary valve showed a significant p-value (P- < 0.05) in age Groups A and age Group C. Mean circumference of aortic valves showed a significant p-value (P- < 0.05) in all age groups except age Group E.Conclusion: The mean circumference of valves are heart in both sexes haves significant differences in most of groups in tricuspid, mitral valve and aortic valves but in case of pulmonary valves age Group A and C showed significant differenceObjective: Analyze cadaveric based data of valves of heart and compare data between male and females of KarachiStudy Design: Descriptive / cross sectional studyPlace and Duration of Study: This study was conducted at the Department of Anatomy, Dow Medical College, DUHS, Karachi from 2008 to 2012Materials and Methods: The hearts of one hundred cadavers (both male and female) were obtained from the morgue of Civil Hospital and other morgues of the Karachi. The hearts were removed in the usual necropsy procedure. Male and female cadaveric hearts were divided into six groups which were constituted ranging in age from 20 to 79 years i.e. Group A: 20-29, Group B: 30-39, Group C: 40-49, Group D: 50-59, Group E: 60-69 and Group F: 70-79. Young and otherwise healthy individuals (died due to road traffic accident, Gunshot injury, Suicide or Homicide) were included in the study. The cadaver whose cause of death was known to be cardiac was not included in the studyResults: The mean circumference of tricuspid valve showed a significant p-value (P- < 0.05) except age Group F. Mean circumference of mitral valve showed a significant p-value (P- < 0.05) in all groups. Mean circumference of pulmonary valve showed a significant p-value (P- < 0.05) in age Groups A and age Group C. Mean circumference of aortic valves showed a significant p-value (P- < 0.05) in all age groups except age Group E.Conclusion: The mean circumference of valves are heart in both sexes haves significant differences in most of groups in tricuspid, mitral valve and aortic valves but in case of pulmonary valves age Group A and C showed significant difference